Requirements Engineering: Foundation for Software Quality: 22nd International Working Conference, REFSQ 2016, Gothenburg, Sweden, March 14-17, 2016, Proceedings - Daneva, Maya; Pastor, Oscar (Lecture notes in computer science, 2016)
Decision Making in Requirements Engineering -- Risk-Aware Multi-Stakeholder Next Release Planning using Multi-Objective Optimization -- Goal-based Decision Making - Using Goal-oriented Problem Structuring and Evaluation Visualization for Multi Criteria Decision Analysis -- Optimizing the Incremental Delivery of Software Features under Uncertainty -- Open Source in Requirements Engineering -- Do Information Retrieval Algorithms for Automated Traceability Perform Effectively on Issue Tracking System Data -- How Firms Adapt and Interact in Open Source Ecosystems: Analyzing Stakeholder Influence and Collaboration Patterns -- Natural Language -- Evaluating the Interpretation of Natural Language Trace Queries -- Indicators for Open Issues in Business Process Models -- Compliance in Requirements Engineering -- Automated Classification of Legal Cross References Based on Semantic Intent -- Deriving Metrics for Estimating the Effort Needed in Requirements Compliance Work -- Requirements Engineering in the Automotive Domain -- Detecting Requirements Defects during a Project Lifetime: an Analysis of a 5-year Automotive Project at Bosch -- Take Care of Your Modes! An Investigation of Defects in Automotive Requirements -- Empirical Studies in Requirements Engineering -- Gamified Requirements Engineering: Model and Experimentation -- Documenting Relations between Requirements and Design Decisions: A Case Study on Design Session Transcripts -- The Use and Effectiveness of User Stories in Practice -- Requirements Engineering Foundations -- Foundations for Transparency Requirements Engineering -- What is essential? - A Pilot Survey on Views about the Requirements Metamodel of reqT.org -- Human Factors in Requirements Engineering -- Peoples' Capabilities are a Blind Spot in RE Research and Practice -- Customer Involvement in Continuous Deployment: A Systematic Literature Review -- Research Methodology in Requirements Engineering -- Common Threats and Mitigation Strategies in Requirements Engineering Experiments with Student Participants -- Lean Development in Design Science Research: Deliberating Principles, Prospects and Pitfalls -- How do We Read Specifications? Experiences from an Eye Tracking Study.